Criminological theory : the essentials - Tibbetts, Stephen G.; Piquero, Alexis Russell (London ; Washington DC : SAGE Publishing, 2023)
"Criminological Theory: The Essentials, Fourth Edition offers students a brief yet comprehensive overview of classic and contemporary criminologists and their theories. Putting criminological theory in context, acclaimed authors Stephen G. Tibbetts and Alex R. Piquero examine policy implications brought about by theoretical perspectives to demonstrate to students the practical application of theories to contemporary social problems. Features and Benefits: The book's brief coverage of the essential topics of criminological theory provides instructors a flexible alternative to larger texts. Case studies examine offender motives to help students apply the theories discussed to interesting and memorable examples. Discussions of policy implications are integrated into each section to allow students to see the practical policy impact of each theory"--
Introduction to the book: an overview of issues in criminological theory -- Preclassical and classical theories of crime -- Modern applications of the classical perspective: deterrence, rational -- Choice, and routine activities or lifestyle theories of crime -- Early positive school perspectives of criminality -- Modern biosocial perspectives of criminal behavior -- Early social structure and strain theories of crime -- The Chicago school and cultural and subcultural theories of crime social process and learning theories of crime -- Social reaction and critical models of crime -- Feminist models of crime -- Life-course perspectives of criminality -- Integrated theoretical models and new perspectives of crime.
Includes bibliographical references and index.
Keywords: Criminology; Crime